EFFECT OF WET GLUTEN ADDITION ON STALIN CHARATERISICS OF BARLEY BREAD - & Naser, Abadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Vital wheat gluten was extracted from broken wheat (Triticum aestivum) and durum wheat (Triticum durum) flour and used to improve the rheological and staling characteristics of bread made using flour from two varieties of barley (IPA 99, IPA 265) which were obtained from the Ministry of Agriculture / Agricultural Research Center. The recent study included seven treatments being, Wheat flour was used as control treatment in bread making (T1), and barley class   IPA99 flour (T2) , IPA 265  flour (T3), IPA99 flour with  durum wheat gluten (T4), , class IPA 265, flour with durum wheat gluten (T5),   IPA99 flour with broken wheat gluten(T6), IPA 265 flour with broken wheat gluten(T7). The bread samples were prepared according to straight dough AACC method No. 10-10 B and the final products were stored for 72 h. (20°C). The obtained results indicated that gradual increase in the bread crust moisture content coincided with a gradual decrease in the moisture content of the bread crumb during the storage period for all treatments.  It has been noticed a significant difference (p≤0.05) among the crumb swelling power values for all treatments, meanwhile all treatments were showed gradual decrease in the swelling power as storage time proceeded ,no significant differences (p≤0.05) in the crumb swelling power between T4 and T5 as compared to the control treatment, for all storage periods. A gradual decrease in the barley bread crumb aqueous suspension sediments amount were observed as the storage period proceeded,  both T4 and T5 treatments showed significant differences (p≤0.05) in sediments amount as compared to the control treatment at all storage periods, this means that T4 and T5 were more resistant to the staling phenomena as compared to other treatments .Therefore,  the durum wheat gluten was more effective in improving barley bread resistance   to staling phenomena as compared to the broken wheat gluten.